ICT tools for research utilized by business education teachers in tertiary colleges of a developing country - Isiyaku, Dauda Dansarki; Mohd Ayub, Ahmad Fauzi; Abdul Kadir, Suhaida (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
This study aims at investigating the types of Information Communication Technology (ICT) tools for research, used by business education teachers in a developing country. A list of 11 ICT tools were provided in four categories, namely: (i) search engine platforms, (ii) survey and polling platforms (iii) cloud storage and computing platforms and (iv) reference management platforms. Respondents were 212 business education teachers from 13 tertiary colleges of Northwestern Nigeria, who were asked to indicate from the list, those ICT tools for research that they often use for classroom purposes. Findings have revealed that out of the 11 ICT tools listed, Google/Google Scholar were used by up to 37.7% of the respondents – implying that these are the most familiar ICT tools for research and perhaps the most commonly used among the teachers. The average percentage of the total users of the 11 research ICT tools listed was only 9.4%, while that of none-users was up to 90.6%. This shows that only a meager number of teachers in business education faculties of tertiary colleges of Northwestern Nigeria make use of ICTs for research. This study is quite informative to school authorities in the developing countries of Africa, especially Nigeria. The study has shown that ICT facilities for research are grossly inadequate in the schools captured in this study, implying that authorities need to provide more of these facilities to schools.